The first 50 contributions to the data observer series: An overview - Joachim Wagner (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2022)
This note gives a short overview of the first 50 contributions to the Data Observer series that were published between 2016 and 2022.2 21 papers deal with data on individuals or household, 12 with data on establishments or enterprises, 2 with linked employer-employee data, 9 cover aggregate data for regions or countries, 3 look at other data, and 3 papers introduce research data centers or data service centers that provide data. Table 1 lists all contributions by the broad categories.
Keywords: 330